The European Educational Policy and Early School Leaving: A Conceptual Analysis from the Perspective of the Leaving Subject - Guerrero Puerta, Laura (Philosophies (Basel), 2023)
This article presents a conceptual analysis of the European educational policy concerning the phenomenon of early school leaving (ESL). It addresses the literature on ESL, emphasizing the importance of studying policies from the perspective of the constructions made of the leaving subject. The concept of lifelong learning is examined, along with its relevance in shaping the subject who leaves within European policies. Additionally, the presence of “double gestures” in educational policies is explored, where, while promoting inclusion, they simultaneously produce exclusion of certain individuals. The influence of the neoliberal approach on the conception of ESL is discussed, and the need to consider alternative approaches to avoid homogenizing the group of young individuals who leave school prematurely is proposed.